TINJAUAN TEKNIK PEWARNAAN ALAMI PADA BATIK BETAWI - Waridah Muthi'ah (Narada : Jurnal Desain dan Seni, 2019)
The increasing public awareness of the dangers posed by the use of synthetic dyes led people to use natural dyes as a solution that are more environmentally friendly. The use of natural dyes in batik is also practiced in Betawi Batik, specifically KBB Setu Babakan in Jagakarsa and Batik Seraci in Bekasi. However, the complicated process, long processing time, and resulting colors that tend to be pale, uneven, and inconsistent pose as a threat to this technique’s sustainability. Based on that premise, research on the development of the potential of natural coloring techniques for batik has become a significant thing. This study aims to record and identify the types of dyes and natural coloring technique in the Betawi Batik’s workshops, in order to examine its strengths, weaknesses, and threats. Thus, a strategy for developing natural dyes can be formulated to support the creation of creative industry products that are more environmentally friendly.